Selection of Packaging Supplier Manufacturing Industry PT. ABC in East Java with An Analytical Hierarcy Process (AHP) Approach - Nicholaus Gede Rio G. M (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted to study and analyze problems related to supplier selection in manufacturing companies. Data collection was carried out by means of interviews, observation and literature study. Data processing uses the AHP approach. The results of data processing using the AHP method can be obtained from several alternative suppliers, namely